Theoretical foundation and numerical analysis on Coandă effect for micro-air vehicle - Ahmed, Riyadh Ibraheem (2016)
Motivated by the need to relate various design parameters of Coandă Micro Air Vehicle (MAV) for its design operation and development, an integrated approach has been undertaken statement that is to develop a workable theoretical analysis that can be utilised as a baseline to design a MAV that can operate effectively in various environmental conditions. The first approach is the analytical, which capitalizes on the basic fundamental principles. The second is the utilization of Computational Fluid Dynamics (CFD), which is based on Navier-Stokes equation for viscous fluid to simulate configurations considered in the analysis, to assess the analytical results, to serve as guideline in developing the analytical model and to provide visualization, and significant insight in identifying the pertinent, problem, to validate the results and to assess the plausibility of the analysis.In the theoretical analysis, care has been taken in identifying the geometrical parameters of the MAV physical properties of the environment and medium, and the motion of the vehicle at the atmosphere. For the motion of the MAV, basic flight dynamics treatment of the vehicle as a free body mass particle has been followed to derive the basic governing equations. The governing equations for Coandă MAV in hover and translatory motion have been developed and given the understanding of the relationships between relevant Coandă MAV parameters for design and operation purposes.The mathematical model and derived performance measures have shown the capability of the theoretical model and analysis in describing the physical phenomena of the flow fields of the semi-spherical Coandă MAV as well as of the cylindrical Coandă MAV. These models provide fundamental tools for the analysis and estimation of Coandă MAV lift generation. In summary, the two approaches have been able to offer the working relationships among various design parameters for the design and operation of Coandă MAV, which are novel and have not been formulated elsewhere as in this work. The results of the analysis are believed to be useful for conceptual or preliminary design sizing of Coandă MAV's, and can be used in the estimation of their lift and other performance measures.